Peningkatan Kemampuan Membaca Permulaan Melalui Metode Drill - Rusmiy Sumanty (Jurnal Didaktika Pendidikan Dasar, 2020)
The purpose of writing best practice is to describe the application of drill methods and Kacamata strategies (beautiful cards of various letters, syllables, and words) in improving the ability to read the1 grade students of elementary school 3 Damar, identify constraints of Drill. Problem-solving strategies used are the drill method and the "kacamata" strategy. The implementation of the drill method is carried out three times a week by taking advantage of 20 minutes before effective learning hours begin, the technical implementation is done by means of peer tutoring and games, while the strategy of glasses (beautiful cards of various letters, syllables, and words) here are in the form of substance or material in learning to read the beginning. Results achieved after filling for 3 stages until the eleventh week, there was significant progress, out of eleven students who were educated all students were able to recognize letters and spell letters into the syllabus, while students who have not been able to spell syllabus into words are only 1 student (0,39%). Based on the data above, it turns out that the Drill method which was carried out in 3 stages for 3 months and combined with The Glasses strategy can improve the ability to read the beginning of students in grade 1 of Elementary School 3 Damar.